2022
DOI: 10.1136/bmjopen-2022-067906
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: Research on Obesity and Diabetes among African Migrants in Europe and Africa Prospective (RODAM-Pros) cohort study

Abstract: PurposeThe Research on Obesity and Diabetes among African Migrants (RODAM) prospective (RODAM-Pros) cohort study was established to identify key changes in environmental exposures and epigenetic modifications driving the high burden of cardiovascular disease (CVD) risk among sub-Saharan African migrants.ParticipantsAll the participants in the RODAM cross-sectional study that completed the baseline assessment (n=5114) were eligible for the follow-up of which 2165 participants (n=638 from rural-Ghana, n=608 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Understanding the drivers behind these disparities may help to mitigate the unequal burden of CVD and identify new causal pathways that contribute to CVD risk in the population at large. 35 To fill some of this knowledge gap, Agyemang et al 36 launched The Research on Obesity and Diabetes among African Migrants (RODAM) prospective (RODAM-Pros) cohort study that was established to identify key changes in environmental exposures and epigenetic modifications driving the high burden of CVD risk among sub-Saharan African migrants. The baseline results indicated that migrants have higher prevalence of CVD risk factors than nonmigrants.…”
Section: Social Determinants Of Health Epigenetics and Cvd Riskmentioning
confidence: 99%
“…Understanding the drivers behind these disparities may help to mitigate the unequal burden of CVD and identify new causal pathways that contribute to CVD risk in the population at large. 35 To fill some of this knowledge gap, Agyemang et al 36 launched The Research on Obesity and Diabetes among African Migrants (RODAM) prospective (RODAM-Pros) cohort study that was established to identify key changes in environmental exposures and epigenetic modifications driving the high burden of CVD risk among sub-Saharan African migrants. The baseline results indicated that migrants have higher prevalence of CVD risk factors than nonmigrants.…”
Section: Social Determinants Of Health Epigenetics and Cvd Riskmentioning
confidence: 99%